22 COVID-19: A review of the impact of the pandemic on ovarian cancer patient advocacy organizations from around the world. (13th November 2020) - Reid, F; MacKay, C
Abstract : Introduction: The World Ovarian Cancer Coalition is a not-for-profit organization that works with patient organizations in 47 countries around the world to ensure that every woman diagnosed with ovarian cancer has the best chance of survival and best quality of life where ever she may live. Methods: Concerned about the impact of COVID-19 on all aspects of their members' work, a survey was conducted as part of a joint effort with four other global cancer coalitions. The consultation was completed by 28 ovarian cancer groups from 16 countries during May 2020. Results: The pandemic has had a significant impact on the work and viability of ovarian cancer patient advocacy organizations. Half (50%) saw an increase in requests for information and support (45% increase on average) mainly relating to treatment and the fear of COVID-19. This coincided with 95% experiencing a sharp decline in income resulting in the need to reduce staff and manage a move to virtual working practices. Of those who fund research, 70% say their ability to fund or carry out research is, or may be, affected. Almost 80% had concerns about their overall current, or future viability. Groups also reported significant disruptions to ovarian cancer services, including delays in access to diagnostics and changes in treatment regimes. Conclusions: Ovarian cancer patient advocacy groups play a vital role in supporting those who are diagnosed with ovarian cancer. The impact of the pandemic means many organizations need additional resources to ensure that they continue to provide these vital services.